Achieving reuse via a generic model of reusable components - Lee, Sai Peck; Rolland, Colette (Taylor & Francis, 2000)
Despite the fact that the field of software reusability has had a significant impact on the engineering of Information Systems (ISs), issues related to the definition of a general purpose reuse model that can serve as a basis of representation for a Repository of Reusable Components (RRC) in generic form for various conceptual modelling techniques of ISs are seldom addressed. A survey of the related research has shown that recent attempts to define reuse models have been limited to those supporting a single ISs methodology. This paper proposes a generic reuse model for taking into account several different ISs methodologies with a single development platform. The generic reuse model not only provides a basis for populating a RRC with reusable components in generic form, but also allows an IS to be conceptualized by reusing the appropriate generic reusable components populated into the RRC through different conceptual models. The generic model provides four concepts for modelling the ideas used in several conceptual models, so that a reusable component extracted through domain analyais with the aid of a conceptual model can be described in generic form or retrieved in the formalism conforming to the appropriate model.